The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages A.M. YULE (Tyne Management Committee, Amalgamated Society of Woodworkers). I would like to pay tribute to the organisers of this Conference. The delegates here have been concentrating upon health in general. I beheve there should be in every industrial undertaking, a sub-committee working from the Joint Production Committee or the Essential Works Order Committee and dealing with the health problems of the men and women in industry. If they do not obtain satisfaction from the managements when they raise complaints, then they should contact the Factory Inspector. If the workers will take courage this afternoon, then I think the solution is in their own hands. I hope, at least, they appreciate this Conference has been worth while. Mrs. AIREY (Winlaton Womens Co-operative Guiid). I agree with everything that has been said by the miners here today. I have a son — my youngest son, who has jaundice and another son working in a pit at Billingham. The first one has to go into hospital next week. He has been ill for several weeks. First he saw a doctor who told him to go to work. Now he has seen another who has ordered him into hospital. I think sometimes that the doctors have the employers' interests at heart and not the workers'. This can be seen in any factory or pit. I would just like to mention the Board of Trade Acts. I remember a young girl in a factory who was going round a factory with the Board of Trade man. She just happened to mention that there were no proper cloakroom facilities. The result was that she got more towels, soap, lavatories and washbasins for the factory. It seems to me that young people do not know sufficient about these Acts. Perhaps a leaflet could be distributed giving particulars of all these things. A MINER. Sanitation is a disgrace in the pit. It is not just a matter of the human element with which we have to contend. We have ponies in the pits and their urine is allowed to flow through the workings. "Nutritional anaemia affects nearly 50 per cent of the women of child-bearing age amongst the poorest paid working class. Infant mortality rate, tuberculosis and some other pathological conditions, which are affected by diet are much higher amongst ill-fed people. Children do not grow to their full stature. The average height of adults amongst the poor is about 4 inches less than amongst the adequately fed well-to-do. Physical disabilities are more common and mental deficiency or mental dullness in children is several times more prevalent. The mortality rate is higher." From "Food and the People" by Sir John Boyd Orr. 17 15X/2/103/295